Achieving price stability : a symposium - Federal Reserve Bank of Kansas City. ([Kansas City, Mo.] : The Bank, 1996)
This publication is a proceeding of a symposium sponsored by the Federal Reserve Bank of Kansas City, Jackson Hole, Wyoming, August 29-31, 1996. The papers, commentary, and discussions at the symposium would provide a better understanding of how central banks can best reduce inflation and what policies and operating procedures should be implemented to maintain price stability.
Includes bibliographical references.
lje 23/08/16
Loan
Keywords: Monetary policy; Price regulation; Economic stabilization